أهمية الرغبة في نجاح تعلم اللغة العربية - Nur Hidayatullah (Imtiyaz : Jurnal Pendidikan dan Bahasa Arab, 2019)
Desire is attention, will and love. The Arabic language is the words in which the Arabs express their purposes, has arrived to us through the transport, and memorized to us the Koran and the hadiths and honest narrated by the trust of the scattered Arabs and their system. Therefore, this Arabic language is important for everyone in the school or the institution of education and outside, because this language is the key to understanding the religious sciences and as a tool of communication between one and the other. The results of this research are that the desire is important in the success of learning Arabic. The steps to success include: Students should know the concept of desire, benefits, elements, and the concept of the Arabic language, and factors affecting the learning of Arabic and others.